Transcriptome Analysis of Wild Bletilla striata Tubers Across Multiple Years Revealed the Molecular Mechanisms Regulating Polysaccharide Metabolism and Tuber Enlargement - Hai Huang; Long Yang; Chunfang Luo; Tuo Qi; Junna Duan (Plants)
A Bletilla striata (Thunb.) Reichb.f., known as Bai Ji in Chinese, is a plant from the Orchidaceae family that has been used for its medicinal properties for thousands of years in China. B. striata holds significant economic value due to its esteemed medicinal applications. Our study aimed to analyze the transcriptome of wild B. striata tubers across multiple years to understand the molecular mechanisms regulating polysaccharide metabolism and tuber enlargement. We collected wild B. striata samples of different growth ages and analyzed their chemical composition, including total phenols, polysaccharides, alkaloids, and proteins. The results showed that the content of these compounds varied with the growth age of the plants. Our study focused on analyzing the genes associated with growth years and accelerating the seedling growth cycle, which holds immense value for the preservation and optimal utilization of superior B. striata orchid resources. To further investigate the underlying molecular mechanisms, we performed a comprehensive transcriptome analysis to explore gene expression, functional annotation, and regulatory networks related to the development and chemical composition of B. striata tubers. The quality of perennial medicinal herbs is intricately linked to their growth age. Unfortunately, excessive wild resource excavation has resulted in the premature harvesting of these herbs, causing a decline in their overall quality and effectiveness. Our study offers valuable insights into the conservation and utilization of B. striata resources.